Effects of injection Shenkang and alprostadil combination on contrast-induced nephropathy in patient with diabetes complicated with mild to moderate renal insufficiency (Bangladesh Journal of Pharmacology, 2017)
The diabetic patients (n=109) with mild or moderate renal insufficiency underwent coronary intervention were randomly divided into control group and observation group. The patients in observation group were treated with injection Shenkang and alprostadil before operation. The results showed that the level of serum creatinine, creatinine clearance and blood urea nitrogen had no significant difference (p>0.05) before and postoperative day 1 and day 2 in both groups. However, the value of serum creatinine, creatinine clearance and blood urea nitrogen were significantly different on post-operative day 3 (p